Issues of Regional Social Innovation - Varga, Krisztina (International Journal of Engineering and Management Sciences, 2017)
Social innovation is not determined as a uniform definition, after a literature review can be defined as follows: social innovation is an innovative and new way of improving community well-being [2]. Social innovation can be defined and measured at micro-, mezo- and macro level similar to technical and economic innovation and plays a key role in the competitiveness. Because of imbalances arising from different levels of economic development, catching-up demand of peripheral settlements have appeared. In addition to the so-called technical innovations, the solution of social problems can be achieved by social tools, methods and new organizations. In catching-up process the local, community level construed innovative ideas and the activities of social innovation play a significant role. The expansion of the innovative areas results in different innovation processes and they can be considered as complementary processes. The social and technical innovation are closely interacting. If there is achange in the economic sphere, social change can occur. This study examines the role of local communities in social innovation at regional level and summarizes the clarifying questions of implementation. Social innovation as a new tool is able to answer daily challenges. The innovative solutions of municipalities, which means new collaborations, result sustainable, flexible and open leadership at regional level. This study will examine the role of governments (or their institutions) in the implementation and generating of social innovation, the tasks of regional innovators and social solutions and models of certain municipalities in Hungary and the European Union.